2021
DOI: 10.3390/ijms22052465
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals in the Prevention of Viral Infections, including COVID-19, among the Pediatric Population: A Review of the Literature

Abstract: In recent years, there has been a growth in scientific interest in nutraceuticals, which are those nutrients in foods that have beneficial effects on health. Nutraceuticals can be extracted, used for food supplements, or added to foods. There has long been interest in the antiviral properties of nutraceuticals, which are especially topical in the context of the ongoing COVID-19 pandemic. Therefore, the purpose of this review is to evaluate the main nutraceuticals to which antiviral roles have been attributed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 234 publications
(282 reference statements)
0
23
0
3
Order By: Relevance
“…The global pandemic caused by COVID-19 has contributed to an increase in these demands from consumers, and set opportunities for food manufacturers to redesign their marketing strategy related to healthy products. Therefore, the scientific literature has pointed to nutraceuticals and functional ingredients as a frontline protection to boost the immune system in the prevention of viral infections, such as COVID-19, in the population, especially young people, as adjunctive therapies [ 2 , 3 ]. Different authors have reported that these benefits can be associated with vitamins (C, D, E), minerals (zinc), melatonin, GABA, and other phytochemicals and functional ingredients, contributing to the disease prevention or control [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global pandemic caused by COVID-19 has contributed to an increase in these demands from consumers, and set opportunities for food manufacturers to redesign their marketing strategy related to healthy products. Therefore, the scientific literature has pointed to nutraceuticals and functional ingredients as a frontline protection to boost the immune system in the prevention of viral infections, such as COVID-19, in the population, especially young people, as adjunctive therapies [ 2 , 3 ]. Different authors have reported that these benefits can be associated with vitamins (C, D, E), minerals (zinc), melatonin, GABA, and other phytochemicals and functional ingredients, contributing to the disease prevention or control [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Lang et al demonstrated that lf inhibits the entry of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) into HEK293E/ACE2-Myc cells and blocks the binding of spike protein [ 36 ]. Consequently, several studies suggested the use of lf for the treatment of SARS-CoV 2 [ 37 ]. In particular, in vitro studies proved the antiviral activity of lf against COVID-19 due to the direct attachment to both SARS-CoV-2 and the cell surface, suggesting the potential role in the management of COVID-19 [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been a growth in scienti ic interest in many nutritional supplements such as Nutraceuticals, which can be extracted, used for food supplements, or added to foods. There has long been interest in the antiviral properties of Nutraceuticals, which are especially topical in the context of the ongoing COVID-19 pandemic [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several nutraceuticals and probiotics may also have some role in enhancing immune functions. One review study [15] on Nutraceuticals also led to the conclusion that the evidence of the ef icacy of nutraceuticals is heterogeneous, and for some of these products, there is no information in the literature to recommend their use. Moreover, Antiseptic gargling and nasal antiseptics are simple preventive measures that has probably been forgotten.…”
mentioning
confidence: 99%